National Consortium for Building Healthy Academic Communities 4th National Summit: Building Cultures of Well-Being Additional Summit Abstracts - BHAC Journal, Building Healthy Academic Communities (Building Healthy Academic Communities Journal, 2020)
No abstract available. Corrigendum Correction of: https://doi.org/10.18061/bhac.v3i2.7286 The authors of the abstract entitled "BUILDING CULTURES OF WELL-BEING: THE HAPPINESS APPROACH" [Building Healthy Academic Communities Journal Vol. 3, No. 2, 2019] inadvertently omitted Danny Twilley (Ohio University) from the list of authors. The author Danny Twilley should have been added after Cara Sidman in the published abstract. The authorship correction is published in Building Healthy Academic Communities Journal Vol. 4, No. 1, 2020, https://doi.org/10.18061/bhac.v4i1.7629.